Proof-of-concept PET imaging of pulmonary sarcoidosis using VAP-1-targeted radiotracer [68Ga]Ga-DOTA-Siglec-9 - Dadson, Prince; Ylä-Outinen, Heli; Kalliokoski, Kari; Tuokkola, Terhi; Malaspina, Simona; Koivumäki, Mikko; Viitanen, Riikka; Rajala, Noora; Silvoniemi, Maria; Tolvanen, Tuula; Nuutila, Pirjo; Jalkanen, Sirpa; et al. (BioMed Central, 2026)
Background
Sarcoidosis is a multisystem granulomatous disease of unknown etiology, with pulmonary involvement being the most common and clinically significant manifestation. Vascular adhesion protein-1 (VAP-1) plays a key role in leukocyte trafficking to inflamed tissues. [⁶⁸Ga]Ga-DOTA-Siglec-9 is a novel PET radiotracer that binds to VAP-1. This proof-of-concept study aimed to evaluate the feasibility of [68Ga]Ga-DOTA-Siglec-9 PET/CT for imaging pulmonary sarcoidosis.
Methods
Six patients with stage 2 pulmonary sarcoidosis (age 50.5 ± 13.1 years; bodyweight 84.2 ± 14.7 kg), diagnosed by clinical, radiological, and histological findings, underwent [68Ga]Ga-DOTA-Siglec-9 PET/CT. Control subjects included six healthy male volunteers (age 37.5 ± 10.3 years; bodyweight 80.3 ± 3.9 kg) and one female patient with lung cancer (age 77 years; bodyweight 62 kg). Tracer uptake was quantified in the lungs, mediastinal lymph nodes, and organs involved in systemic inflammation.
Results
Patients with sarcoidosis showed significantly higher [68Ga]Ga-DOTA-Siglec-9 uptake in the lungs (SUVmean 1.82 ± 0.52 vs. 0.41 ± 0.08; P = 0.00006) and mediastinal lymph nodes (SUVmean 2.06 ± 0.46 vs. 0.89 ± 0.26; P = 0.0003) compared to healthy controls. Increased uptake was also observed in the liver (SUVmean 1.18 ± 0.14 vs. 0.80 ± 0.10, P = 0.0003), spleen (SUVmean 1.13 ± 0.09 vs. 0.82 ± 0.06, P = 0.00003), bone marrow (SUVmean 0.30 ± 0.12 vs. 0.06 ± 0.05, P = 0.001), and bone (SUVmean 0.27 ± 0.11 vs. 0.08 ± 0.04, P = 0.004), indicating systemic inflammation.
Conclusions
This proof-of-concept study demonstrates the potential of VAP-1-targeted [68Ga]Ga-DOTA-Siglec-9 PET/CT for imaging pulmonary sarcoidosis and associated inflammatory activity. Further validation in larger cohorts are warranted.